Conformity and Positive Emotions as Predictors of Impulsive Buying Tendencies of Online Shopping Consumer - Lania Muharsih; Linda Mora; Cempaka Putrie Dimala; Wina Lova Riza (Edutran, 2023)
In this digital era, people increasingly prefer to engage in easy activities, such as online shopping. Impulsive buying is a phenomenon that occurs unconsciously in daily life, both by men and women. The age group of 18-21 years old, particularly adolescents, tend to engage in impulsive buying more than other age groups. Therefore, this research aims to investigate the influence of conformity and positive emotions as predictors of consumer impulsive buying tendencies in online shopping in Karawang. The research method used in this study is an associative quantitative method. The research instruments include a 42-item conformity scale, a 38-item positive emotions scale, and a 23-item impulsive buying tendency scale. The population of this study is online shoppers aged 18-21 years old in Karawang. The sampling technique used is quota sampling with a sample size of 385 people. The data analysis technique used is multiple linear regression test using JASP 0.16 software. Based on the data analysis, the significance value obtained was < 0.001 or p < 0.05, indicating that conformity and positive emotions can influence the tendency of consumer impulsive buying in online shopping in Karawang as predictors. The influence contributed by conformity and positive emotions towards the tendency of consumer impulsive buying in online shopping in Karawang is 20.4%, while the remaining 79.6% is influenced by other variables outside the scope of this research.